(untitled) (Research, Society and Development, 2020)
This study aimed to dry the rhizomes of Curcuma longa L. applying mathematical modeling, determined the antimicrobial activity and toxicity of the essential oil (EO) obtained after the drying process applied. The collected plant material was submitted to convective drying kiln at 45 °C. Mathematical models were applied to represent the drying process and statistical analysis performed using the statistica software 10. The EOs were obtained through the hydrodistillation technique and antimicrobial activity by the Disc Diffusion and Dilution Method in Broth against Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa and Salmonella sp. For the toxicity test, the Artemia salina bioassay was applied. Through the results obtained it was possible to determine that Logarithm’s mathematical model was the one that best fit the experimental data. The EO showed bactericidal activity against all microorganisms tested. The toxicity test proved the toxicity of EO with a LC50 greater than 250 mg/L. The results obtained prove the potential required for the application of EO of C. longa rhizomes as antimicrobial, and is still non-toxic to non-target organisms.